Dung beetle fauna from Mount Mabu, Mozambique. Part 1: A new species of Onthophagus Latreille, 1802, and a checklist of species belonging to group 3 (d’Orbigny 1913) (Coleoptera: Scarabaeidae: Scarabaeinae) - Daniel, Gimo M.; Strümpher, Werner P.; Josso, Jean-François (Zootaxa, 2023)
Onthophagus mabuensis Daniel, Strümpher & Josso, new species, is diagnosed, described and illustrated from Mount Mabu, which is situated in north-central Mozambique. Morphological comparison is made between this new forest species and similar species from Malawi and Zambia in group 3 of Onthophagus Latreille, 1802, as classified by d’Orbigny (1913). In addition, we provide a checklist of all known group 3 species.